HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN KEJADIAN ABORTUS DI WILAYAH KERJA PUSKESMAS BEBESEN KABUPATEN ACEH TENGAH - Rahma Yani; nurlaely (Jurnal Ilmiah Cerebral Medika, 2022)
Abortion is a threat or expulsion of the products of conception meeting egg and sperm cells at a gestational age of less than 20 weeks or a fetus weighing less than 500 grams, before the fetus can survive outside the womb. This is a process of ending the life of the fetus before it is given the opportunity to grow. If the fetus is born alive (live) before 28 weeks but after 20 weeks, then the term is premature birth (Manuaba, 2013). The initial survey that the researchers conducted on pregnant women at the Bebesen Health Center. The aim of the study was to determine the relationship between knowledge of pregnant women and the incidence of abortion in Bebesen Public Health Center, Central Aceh District. This research is descriptive analytic, namely the research method carried out to create an objective picture of a situation. With a cross sectional approach, namely a research approach where data collection for independent variables and dependent variables is collected at the same time or within a certain period (Notoadmodjo, 2012). as many as 74 respondents (92.5%). Based on table 2, it shows that the majority of pregnant women's knowledge about the incidence of abortion at the Bebesen Health Center, Central Aceh Regency is in the less category, namely 46 respondents (57.5%) of 80 respondents. From the results of research and discussions that have been carried out on June 22 to 25, 2015, it can be concluded that there is no relationship between knowledge of pregnant women and the incidence of abortion. Where the value obtained is P value = 0.170. It is hoped that further researchers will be able to conduct research with a larger sample size and more in-depth theory so that the results achieved are more accurate.Based on the results of data collection obtained the number of respondents as many as 80 people. Based on table 5.1 the number of pregnant women who did not experience an abortion at the Bebesen Health Center, Central Aceh Regency, was 74 respondents (92.5%). Based on table 5.2 shows that the majority of pregnant women's knowledge about the incidence of abortion at the Bebesen Health Center, Central Aceh Regency is in the less category, namely 46 respondents (57.5%) of 80 respondents. From the results of research and discussions that have been carried out on June 22 to 25, 2015, it can be concluded that there is no relationship between knowledge of pregnant women and the incidence of abortion. Where the value obtained is P value = 0.170. It is hoped that further researchers will be able to conduct research with a larger sample size and more in-depth theory so that the results achieved are more accurate.